Postoperative Tongqi Formula ameliorates postoperative ileus via p38 MAPK signaling pathway and metabolic disorder - Mengmeng Yang; Yuxuan Lu; Shufan Jin; Wanqiu Liu; Miaoshi Yao; Zhiwei Jiang; Yachun Shu (Heliyon)
Aim of the study: This study investigated the mechanism by which the Postoperative Tongqi Formula (PTQF) treats postoperative ileus (POI) through regulation of the p38 MAPK signaling pathway, Zona occludens 1 (ZO-1) protein, and metabolism. Methods: The primary components of PTQF were characterized using UHPLC-Q-TOF-MS/MS. The identified compounds subsequently employed network pharmacology to predict the signaling pathways associated with the inflammatory phase of POI. The anti-inflammatory effects of PTQF were evaluated in vitro using RAW264.7 cells. A rat model of POI was used to assess efficacy based on the spleen index and charcoal powder propulsion rat in the small intestine. Furthermore, pathological damage to the small intestine was analyzed using hematoxylin and eosin (HE) staining as well as immunofluorescence to evaluate ZO-1 protein expression. Inflammatory cytokine levels were quantified using enzyme-linked immunosorbent assay (ELISA). Subsequently, Western blot analysis was performed to examine the p38 MAPK signaling pathway. Finally, a metabolomics approach was employed to analyze serum samples to identify potential metabolic pathways. Results: A total of 130 chemical constituents were identified in PTQF. Following the network pharmacology analysis of these compounds, the p38 MAPK signaling pathway was chosen for further investigation. In vitro, PTQF effectively inhibited inflammatory responses in RAW264.7 cells. Results from the spleen index and charcoal powder propulsion rate indicated that PTQF alleviated the inflammatory phase of POI in rats by mitigating systemic and intestinal inflammation. This was supported by reduced levels of inflammatory factors, modulation of ZO-1 protein expression, and a decrease in p38 MAPK phosphorylation levels. Furthermore, serum metabolomics revealed nine differential metabolites linked to intestinal inflammation. Conclusion: PTQF mitigates inflammation and intestinal damage in POI rats by modulating inflammatory factors, ZO-1 protein expression, the p38 MAPK signaling pathway, and metabolic disturbances.